REVIEW TIDUR DAN GANGGUAN TIDUR - Rizak Tiara Yusan; Synta Haqqul Fadlilah (Fakultas Kedokteran Universitas Jenderal Soedirman, 2022)
Sleep is a sedentary mental and physical condition. Sleep is necessary for emotional, physical, and cognitive well-being and accounts for approximately one-third of a person's life. Sleep happens in cycles in which the body alternates between two modes: REM sleep and non-REM sleep. Behavioural observation, physiological monitoring, or a mix of the two can be used for the assessment of sleep and wake. Current clinical recommendations for scoring PSGs describe three phases of progressively. The majority of hormones in plasma show strong 24-hour cycles, highlighting the significance of the circadian clock and sleep-related impacts on hormone release and/or metabolism. Lack of sufficient sleep for duration or quality might affect one's ability to function normally and maintain good health. The typical adult requires seven or more hours of sleep each night to be healthy. This report will inform the current state of the science of sleep and sleep deprivation.